Inimici nostri: Jews as heretics and heretics as judaizers in Jerome and Augustine - Hood, John Y.B. (Vox Patrum, 2018)
In their polemical as well as their ostensibly non-polemical writings, SS. Jerome and Augustine refer to the Church’s enemies as an unholy triad: Jews, pagans, and Christian heretics. These inimici, they assert, are linked by their common failure to accept the Gospel of the orthodox Catholic Church, as well as by the root cause of their unbelief: pride, which leads them to resist the truth. In this article, I focus on the links Jerome and Augustine purport to find between Judaism and Christian heresy. I draw from polemical and non-polemical works by both writers, including Jerome’s biblical commentaries and anti-Pelagian treatises, and Augustine’s De Civitate Dei as well as his writings adversus Jews, Donatists, and Pelagians. In addition to identifying the doctrinal commonalities that Jerome and Augustine assert exist between Judaism and Christian heresy, I examine the often-similar rhetorical devices employed by both writers in their denunciations of these inimici. The article concludes by speculating on the possible roots of these denunciations in the authors’ doubts and insecurities, and notes that, paradoxically, Jerome and Augustine’s epistemological doubts regarding divine election led them to retain a measure of hope for their theological enemies, and so to counsel tolerance toward them.